2017
DOI: 10.1097/bcr.0000000000000463
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Socioeconomic Status and Parental Demographics on Activation of Department of Child and Family Services in Pediatric Burn Injury

Abstract: Burns resulting from child maltreatment are tragic causes of significant morbidity and mortality, most commonly affecting children under 3 years of age. More than one third of nonaccidental burns occur in single-parent homes or have parents with history of mental illness, substance abuse, incarceration, or Department of Children and Family Services (DCFS) involvement. The authors sought to profile pediatric burn injuries associated with DCFS investigations. They performed a retrospective chart review of pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“… 7 In earlier studies on burns etiology carried out by many researchers, hot liquid burns have been found to be most common, whereas burns from direct contact with flames take second place. 1 , 3 , 7 , 9 - 11 In our study, hot water and tea burns took first place (85%), with dairy product burns taking second place (11%), in contrast to many earlier studies in which direct flame burns take second place. This finding may be attributed to that the majority of our burn cases (85%) were from families living in rural areas where animal husbandry is common, and where the relationship between dairy products and floor furnace burns and females was found to be statistically significant (p <0.05).…”
Section: Discussioncontrasting
confidence: 88%
“… 7 In earlier studies on burns etiology carried out by many researchers, hot liquid burns have been found to be most common, whereas burns from direct contact with flames take second place. 1 , 3 , 7 , 9 - 11 In our study, hot water and tea burns took first place (85%), with dairy product burns taking second place (11%), in contrast to many earlier studies in which direct flame burns take second place. This finding may be attributed to that the majority of our burn cases (85%) were from families living in rural areas where animal husbandry is common, and where the relationship between dairy products and floor furnace burns and females was found to be statistically significant (p <0.05).…”
Section: Discussioncontrasting
confidence: 88%
“…Lane et al retrospectively reviewed children admitted for skull or long bone fractures and found that minority children between 1 and 3 years old were significantly more likely to be referred to CPS compared with their non-Hispanic white counterparts (adjusted OR 4.32, 95% CI 1.63–11.43, P = .003) [ 11 ]. The burn literature mirrors this finding: Campos et al reported that nonwhite race/ethnicity was associated with increased odds of CPS referral in pediatric burns [ 9 ].…”
Section: Discussionmentioning
confidence: 85%
“…Hodgman et al narrowly categorized NABs as burns secondary to intentional injury inflicted by another person and therefore reported a low rate of 5.3% [ 8 ]. Campos et al broadly defined NABs as a burn with concurrent CPS involvement and, therefore, reported a much higher rate of 22.5% [ 9 ]. As expected, our rate falls in between these estimates because burns secondary to neglect were included in our definition of NAB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations